The formation of cucumber resistant plants Cucunzis sativus of Rhizoctonia solani calves and stems - Ansam Sadoon; Adnan Abdullah (College of Education for Pure Sciences, 2007)
In this study callus stimulated from cotyledons and stem explants of cucumber seedlings on MS media supplemented with 2.0 mg/L of BA and 1.0 mg/ L of NAA for cotyledons , while in stem MS media containing 1.0 mg/L from BA and NAA were used . Selection of resistant callus to the virulent strains of Rhizoctonia so/ani was examined from culture of cotyledons and stem medium contained the concentrations 1.0, 5.0, 10.0, 15.0, 20 and 25% of fungal filtrates. The best concentrations which allowed selection after three cycles ( 20 days I cycle) of selections were 10 and 15% . The resistant callus showed a high level of peroxidases enzymes activity . Resistance callus of cotyledons and stems were regenerated on MS medium containing 4.0 mg/L of BA and 0.1 mg/L NAA in spite of reduction of the regeneration ability of the resistant callus up to half in cotyledons and stems compat~d-with the control plants. Regenerated stems formed roots on MS medium without grouth regulators . Cucumber plants regenerated from callus tolerating toxic filtrates exhibited resistance when infected with pathogenic fungi .